The role of vitamers and dietary-based metabolites of vitamin D in prevention of vitamin D deficiency - Kevin D. Cashman (Food & Nutrition Research, 2012)
There is little doubt that vitamin D deficiency across all age groups in Europe is a problem. Low vitamin D status arises due to limited, if any, dermal synthesis during the winter months at latitudes above 40°N, putting increased importance on dietary supply of the vitamin. However, dietary intakes by most populations are low due to the limited supply of vitamin D-rich foods in the food chain. Thus strategies that effectively address this public health issue are urgently required. It has been emphasized and re-emphasized that there are only a limited number of public health strategies available to correct low dietary vitamin D intake: 1 improving intake of naturally occurring vitamin D-rich foods, 2 vitamin D fortification (mandatory or voluntarily) of food, and 3 vitamin D supplementation. Recent evidence suggests that the levels of vitamin D added to food would need to be high so as to ensure dietary requirements are met and health outcomes optimized. In addition, knowledge of the most effective forms of vitamin D to use in some of these preventative approaches is important. There is still uncertainty in relation to the relative efficacy of vitamin D2 versus D3, the two main food derived forms and those used in vitamin D supplements. The major metabolite of vitamin D with biological activity is 1,25(OH)2D; however, this is usually used for pharmacological purposes and is not typically used in normal, healthy people. The other major metabolite, 25(OH)D, which has also been used for pharmacological purposes is present in certain foods such as meat and meat products (particularly offal) as well as eggs. This metabolite may have the potential to boost vitamin D status up to five times more effectively that native vitamin D3 in foods. However, the exact bioactivity of this compound needs to be established.